The power dynamics and politics of survey design: measuring workload associated with teaching, administering and supporting work-integrated learning courses. Issue 6 (2nd June 2016) - Clark, Lindie; Rowe, Anna; Cantori, Alex; Bilgin, Ayse; Mukuria, Valentine
Abstract : Work-integrated learning (WIL) courses can be more time consuming and resource intensive to design, teach, administer and support than classroom-based courses, as they generally require different curricula and pedagogical approaches as well as additional administrative and pastoral responsibilities. Workload and resourcing issues are reported as key challenges to the implementation of WIL, but most of the evidence to date is anecdotal. Accurately quantifying workload associated with WIL is difficult, because teaching and administrative roles can be so interconnected. To address this gap in the literature and inform institutional practice, a study was initiated at an Australian university to collect empirical data on the type and amount of work involved in delivering WIL courses. This paper describes the process of survey development, including literature review, extensive consultation phase and pilot study, all of which had to take account of the inherent power dynamics, politics and sensitivities around measuring staff workload.